The Concept of Quality in Curriculum: A Review of The Literature on Determining Curriculum Quality - Ibad, Wasilatul (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2024)
The curriculum is a description of what students should learn in school. The curriculum itself includes many subjects and objects to be applied in educational institutions. Teachers, material subjects, students, and many other things are required to achieve worthwhile and useful learning outcomes and then realize the aim of education. The quality of the curriculum is important to the success of education in order to create students who become good people in society. This paper discusses the concept of quality in curriculum education in general. The aim of the research is to clarify the perception of curriculum quality based on references to international and national curricula. The authors used qualitative research with literature review technique compilation data. This paper summarizes the views and perceptions of national curriculum and UNESCO curriculum quality by analyzing the curriculum implemented in Indonesia. The result revealed that the quality of the curriculum has four criteria (development, the curriculum, the implementation, and evaluation) that are then developed to obey the education national standard (SNP): competence of graduates standards, contents standards, process standards, and assessment standards. Based on the data, almost 70% of the implementation of the development and improvement of the Merdeka Indonesia curriculum is going well. To date, there are 293,373 formal education units that have implemented the Merdeka curriculum optimally.